2011
DOI: 10.1136/jmg.2010.088310
|View full text |Cite
|
Sign up to set email alerts
|

Hearing function and thresholds: a genome-wide association study in European isolated populations identifies new loci and pathways

Abstract: Background Hearing is a complex trait, but until now only a few genes are known to contribute to variability of this process. In order to discover genes and pathways that underlie auditory function, a genome-wide association study was carried out within the International Consortium G-EAR. Methods Meta-analysis of genome-wide association study's data from six isolated populations of European ancestry for an overall number of 3417 individuals. Results Eight suggestive significant loci (p<10 À7) were detected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 38 publications
1
90
1
Order By: Relevance
“…None of the top-ranked SNPs in our study were statistically significant in any of the previous GWASs on ARHI. 4,5 To look for evidence of replication of previous studies, we first looked up the P-values for all individual SNPs that were reported to be significant in the previous GWASs and checked their significance in the current study. For the GWAS by Girotto et al, 5 this included the SNPs having a P-value below 10e À5.…”
Section: Common Variant Analysismentioning
confidence: 99%
“…None of the top-ranked SNPs in our study were statistically significant in any of the previous GWASs on ARHI. 4,5 To look for evidence of replication of previous studies, we first looked up the P-values for all individual SNPs that were reported to be significant in the previous GWASs and checked their significance in the current study. For the GWAS by Girotto et al, 5 this included the SNPs having a P-value below 10e À5.…”
Section: Common Variant Analysismentioning
confidence: 99%
“…[28][29][30] In brief, INGI-CARL, INGI-FVG and INGI-VB have been genotyped with Illumina 370 k highdensity SNP array, whereas SR has been genotyped with Illumina 700 k highdensity SNP arrays. Genotype imputation on the INGI cohorts and SR was conducted after standard QC using SHAPEIT2 31 for the phasing step and IMPUTE2 32 for the imputation using the 1000 Genomes phase I v3 reference set.…”
Section: Genotyping and Imputationmentioning
confidence: 99%
“…Moreover, a few single-gene, late-onset, dominant mutations have also been described, but these are rare, confirming the difficulties in dissecting the molecular basis of ARHL. Furthermore, quite recently, some genes associated with hearing functions, which might also play a role in ARHL, have been identified [32] . Finally, relatively few animal models of hearing impairment …”
Section: Age-related Hearing Lossmentioning
confidence: 99%